THE EFFECT OF TEACHER COMPETENCE ON THE QUALITY OF LEARNING IN SMP NEGERI 5 GORONTALO - novita monoarfa; Imam Mashudi; Aryati Hamzah (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to determine the effect of teacher competence on the quality of learning in SMP Negeri 5 Gorontalo.This type of research is descriptive research with a quantitative approach. The type of data used is primary data and secondary data with data sourced from observations, questionnaires and documentation. The population in this study amounted to 30 teachers.The results of this study were hypothesis testing in order to be able to test the influence of teacher competence on the quality of learning to have a positive and significant effect on the quality of learning at SMP Negeri 5 Gorontalo. This is shown from the analysis of hypothesis testing data, resulting in a positive regression coefficient of 0.459 and a significant level of 0.459 > 0.05 so that it can be concluded that teacher competence has a positive effect on the quality of learning in SMP Negeri 5 Gorontalo.